Influences of viewing nature through windows - Abkar, Mahdieh; Mohd Shariff, Mustafa Kamal; Maulan, Suhardi; Mariapan, Manohar (American-Eurasian Network for Scientific Information, 2010)
A number of studies have found relationships between nature and people’s health. These studies indicated three levels of engagement including viewing, being and involvement with nature which positively impact health. Nevertheless, few studies have focused on the effectiveness of viewing nature through windows on human health. This paper will summarize and analyze studies dealing with viewing nature through window. These include viewing nature through windows in formal building, the workplace, and the home. Results indicated that many aspects of human health and development can be significantly improved by viewing nature through window. Improvement in concentration, recovery from stress, high productivity, and improvement in psychological state are all positively associated with viewing nature. These findings are significant for architects and town planners in designing structures with adequate views of nature. However, research in this area is far from conclusive and this paper recommends directions for future studies as regards nature views through windows.